Stem cell therapy for hereditary breast cancer - Rassi, H. (Цитология и генетика, 2009)
In this study, we report on recent advances on the functions of embryonic, fetal, and adult stem cell progenitors for hereditary breast cancer therapies. Severalmolecular targeting therapies are described by activation and blocking distinct developmental signaling cascade elements, such as BRCA1, EGFR,hedgehog, Wnt/β catenin, and/or Notch pathways, which are frequently upregulated in cancer progenitor cells during the initiation and development of breast cancer.